Regulatory Coherence In Digital Zakat Governance Using Simulation Framework Indonesia - Farrel Izham Prayitno (Universitas Islam Darul 'ulum Lamongan, 2026)
The rapid expansion of digital financial ecosystems has transformed zakat governance by integrating sharia principles, state regulations, and fintech platforms, yet this transformation has created challenges in achieving regulatory coherence across these domains. This study aims to analyze and construct a regulatory coherence framework for digital zakat governance in Indonesia by examining the alignment between normative, legal, and institutional dimensions. Using a qualitative-analytical approach based on secondary data and a rule-based simulation framework, the study evaluates regulatory instruments through three dimensions: normative alignment, legal integration, and institutional coordination. The findings show that digital zakat governance exhibits a moderate level of regulatory coherence, with strong normative alignment but weaker legal integration and institutional coordination. The simulation results indicate that inconsistencies primarily arise from fragmented legal frameworks and limited interaction among regulatory actors, particularly in fintech-based zakat systems. These findings contribute theoretically by operationalizing regulatory coherence within Islamic economic law and practically by providing a structured model for improving governance and policy design. The study highlights the importance of integrating maqasid-based principles with adaptive regulatory mechanisms to ensure effective and sustainable digital zakat governance.